2019
DOI: 10.1002/cbf.3382
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of scarring formation mediated by human Tenon fibroblasts: Effect of Y‐27632, a Rho kinase inhibitor

Abstract: Scar formation is the most common cause for failure of glaucoma filtration surgery because of increased fibroblast proliferation and activation. We have now examined the effect of Y‐27632, a Rho‐associated protein kinase (ROCK) inhibitor, on postsurgical scarring formation in human Tenon fibroblasts (HTFs). Collagen gel contraction assay was used to compare contractility activity of Y‐27632 with several antiglaucoma drugs. Immunofluorescence and western blotting were used to examine expression of scar formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
(161 reference statements)
3
17
1
Order By: Relevance
“…AR12286 reduced the phosphorylated SMAD2 expression that is induced by TGF-β1. These findings differ from findings reported by Meyer-ter-Vehn et al (2006) and Ibrahim et al (2019) [ 3 , 41 ]. Meyer-ter-Vehn et al explored the p38-dependence of TGF-β-induced myofibroblast transdifferentiation and provided a mechanism for the effect of H1152 on α-SMA expression.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…AR12286 reduced the phosphorylated SMAD2 expression that is induced by TGF-β1. These findings differ from findings reported by Meyer-ter-Vehn et al (2006) and Ibrahim et al (2019) [ 3 , 41 ]. Meyer-ter-Vehn et al explored the p38-dependence of TGF-β-induced myofibroblast transdifferentiation and provided a mechanism for the effect of H1152 on α-SMA expression.…”
Section: Discussioncontrasting
confidence: 98%
“…Compared with treatment using other ROCK inhibitors, AR12286 treatment requires lower concentrations (250 and 500 nM). A study reported that 5 to 10 μM ROCK inhibitors were required for myofibroblast differentiation [ 35 , 41 ]. However, drug concentrations may prove to be a limitation of AR12286.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic possibilities for Rip will be also expected for the treatment of corneal endothelial dystrophy and inflammation of retinal pigment epithelium [ 53 , 54 ]. Furthermore, previous studies, using 2D cultured HconH cells [ 55 ] as well as human tenon fibroblasts [ 56 ], have demonstrated that Rip and other pan-ROCK-is also induce beneficial effects toward conjunctival fibrosis formation. Here, the findings reported herein reveal additional proof of the effects of ROCK-is, Rip and KD025 toward conjunctival fibrogenetic changes by a direct measuring stiffness of the 3D HconF cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that in vitro administration of Y-27632 protects against post-surgical scarring by reduction of collagen gel contraction, unlike other anti-glaucoma drugs, eg timolol, latanoprost, which may induce fibrosis. 31 This agent prevented fibrosis through inhibition of both the transdifferentiation of Tenon fibroblasts into activated myofibroblasts and TGF-β 1 signaling through suppression of the mitogen‐activated protein kinase (MAPK) pathway. 31 …”
Section: Rock Inhibitors and Their Role In Glaucomamentioning
confidence: 99%
“… 31 This agent prevented fibrosis through inhibition of both the transdifferentiation of Tenon fibroblasts into activated myofibroblasts and TGF-β 1 signaling through suppression of the mitogen‐activated protein kinase (MAPK) pathway. 31 …”
Section: Rock Inhibitors and Their Role In Glaucomamentioning
confidence: 99%